Positive solutions for three-point semipositone boundary value problems with convex nonlinearity - Zhang, Xinguang (Springer, 2009)
In this paper, we consider the existence of positive solutions for a class of singular three-point semipositone boundary value problems with convex nonlinearity. By employing a well-known fixed point theorem, some new existence results are given under the case where nonlinearity can be sign-changing and have finitely many singularities.